The power of ultimate Six Sigma : Keki Bhote's proven system for moving beyond quality excellence to total business excellence - Bhote, Keki R., 1925-2013 (AMACOM, 2003)
One of Six Sigma's founding fathers shares his trademarked process for ensuring total quality.